Places of emptiness in the novel The Man who sleeps by Georges Perec and its film adaptation (Colloquia Comparativa Litterarum, 2025)
This text examines George Perec's novel The Man Who Sleeps and its adaptation through a young man's existential crisis in search of the meaning of his existence. The disintegrated time and space introduce the reader to the labyrinth of wandering consciousness through the “rhetorical places”, the delight of emptiness, on the border between dream and reality. The work is close to the experiment of the literary movement “New Novel”, approaching in the film the “camera-pen” embodied in the New Wave of French cinema.
Keywords: New Novel; New Wave; rhetorical places; emptiness; existential crisis